Respostas

A melhor resposta!
2013-09-09T19:05:51-03:00
a) 2x+5=x-3
2x-x = -3-5
x = -8

b) 3x+7=2x-4
3x-2x = -4-7
x = -11

c) x-7=2x+5
-7-5 = 2x-x
-12 = x
x = -12

d) 5x+10=2x+19
5x-2x = 19-10
3x = 9
x = 9/3
x = 3

e) 4x-5=-2x-2
4x+2x = -2+5
6x = 3
x = 3/6   OBS: Simplificando 3 e 6 por 3 temos:
x = 1/3


f) 2 * (x+1)+5=x-3
2x+1+5 = x-3
2x-x = -3-1-5
x = -9


2 5 2
2013-09-09T19:08:56-03:00
C)X-2x=5+7
3x=12
x=12/3
X=4


D)5x-2x=+19-10
3x=9
x=9/3
x=3


E)4x+2x=-2+5
6x=3
X=3/6
X=3

F)2x+2+5=x-3
2x-x=-3-2-5
1x=-5-5
1x=-10
x=-10/1
x=-10

Espero ter ajudado !!
2 3 2